2019
DOI: 10.1111/jmwh.12965
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Women's Experiences in Accessing, Understanding, Appraising, and Applying Health Information During Pregnancy

Abstract: Introduction: This study explored pregnant women's experiences in accessing, understanding, evaluating, communicating, and using health information and services during pregnancy.Methods: Pregnant participants (aged 18-45 years) were recruited from an obstetrics and gynecology department of a large urban training hospital. Focus groups were facilitated by a moderator's guide developed from health literacy domains (access, understand, evaluate, and communicate and use), audio recorded, transcribed, and uploaded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 35 publications
4
44
0
Order By: Relevance
“…In addition to the easy understanding of information, patients in the present study also praised the way in which it was transmitted. The study results reinforce the need to invest in health education as a way to offer autonomy, empowerment and health literacy (11,12). Within the collective, the external social in uence on the individual's risk perception can be seen in the valuation of certain diseases.…”
Section: Discussionsupporting
confidence: 65%
“…In addition to the easy understanding of information, patients in the present study also praised the way in which it was transmitted. The study results reinforce the need to invest in health education as a way to offer autonomy, empowerment and health literacy (11,12). Within the collective, the external social in uence on the individual's risk perception can be seen in the valuation of certain diseases.…”
Section: Discussionsupporting
confidence: 65%
“…In addition to easy understanding of the information, patients in the present study also praised the way it was transmitted. The study results reinforce the need to invest in health education as a way to offer autonomy, empowerment and health literacy (14) (15). Within the collective, the external social in uence on the individual's risk perception can be perceived in the valuation or not of certain diseases.…”
Section: Discussionsupporting
confidence: 63%
“…In this regard, Svensson et al (2016) reported that embarrassment and taboos related to sexual health issues gave rise to knowledge gaps and misconceptions about sexual health [4]. A woman's ability to fulfill her informational needs depends on her access to various information sources and appreciating the related information [37]. In this study, to appreciate the obtained information, participants searched various sources and asked questions from the informants.…”
Section: Discussionmentioning
confidence: 93%
“…A woman’s ability to fulfill her informational needs depends on her access to various information sources and appreciating the related information [ 37 ]. In this study, to appreciate the obtained information, participants searched various sources and asked questions from the informants.…”
Section: Discussionmentioning
confidence: 99%